Inter-cofactor protein remodeling rewires short-circuited transmembrane electron transfer - Deborah K. Hanson; James C. Buhrmaster; Ryan M. Wyllie; Gregory A. Tira; Kaitlyn M. Faries; Dewey Holten; Christine Kirmaier; Philip D. Laible (Communications Chemistry)
Abstract Intraprotein electron transfer (ET) requires explicit local control of the environment of cofactors to influence their intermolecular distances, relative orientations, and redox properties. Efficient, longer-range ET often utilizes molecular orbitals of aromatic residues present in the intervening space. Here, revitalization of a vestigial ET pathway in the bacterial photosynthetic reaction center is achieved by scanning with tryptophans to uncover markedly improved routes of electron conduction in a key stabilizing step spanning 15 Å between tetrapyrrole and quinone cofactors. This ET event is maximally enhanced by pairing one or more tryptophans with a threonine to influence quinone binding and/or redox potential. Synergistic effects of these substitutions increase the yield of that ET step to ~95%. Joining these substitutions with mutant residues that improve initial ET steps dramatically enhances transmembrane charge separation via this redesigned version of a pathway that is quantitatively inactive in the native protein-cofactor complex.